Ground Rent in Argentina: Export Duties, Period 2003-2014 (2018)
This article aims to contribute to the research concerning export taxes relevance in the Argentine economic process, based on the analysis on the general determinants of the tax and on the events that occurredduring the period after the convertibility. A wide range of information is used in order to estimate tax collection, complementing the official information. In particular, the obtained estimation has a higher levelof disaggregation. At the same time an alternative classification of the economic activities over which the tax actually impacts is proposed, and the effect of the refunds over exports is incorporated. Among the results, it is found that the relevance of the tax collection in the aforementioned period is one of the the largest in historical terms and strongly associated with the ground rent due to exploitation of natural resources.